O comportamento de crianças com Transtorno do Espectro Autístico no contexto de educação musical: estudo de caso - ESPÍRITO SANTO, Lady Anny Araújo do (Universidade Federal do Pará, 2014)
The Autistic Spectrum Disorder (ASD) is a complex syndrome, with higher prevalence in males, where the difficulties are manifested before the age of three and focus on three main areas: qualitative deviations in communication, social interaction and repetitive and stereotyped behavior. Using the context of music education, this study aimed to describe the behavior of two autistic children in the context of music lessons (percussion). For this purpose, was developed the Observation of Protocol Child with Autistic Spectrum Disorder in the Context of Classroom Music (percussion) from the analysis of behaviors emitted by children in the moments before and during class, recorded on audio and video. The categories that make up this protocol include the main features of the frames of TEA, which were expressed during music lessons in moments of interaction with adults and with peers, as well as the answers given by the tasks. The behavior of each child were recorded, according to the categories proposed, noting the frequency with which they occurred. The results indicate that the child A, non-verbal, had a higher frequency to respond functionally to the initiatives of adult interaction, initiate functional interactions with adults and decline repetitive and stereotyped behavior, throughout the classes. Child B, verbal, showed higher frequency to initiate non-adaptative interactions with adults, to respond with non-adaptative answers to adults and maintenance of repetitive and stereotyped behavior in the course of lessons.